Market Structure and Technological Progress: The Influence of Monopoly on Product Innovation - Swan, Peter L. (Quarterly Journal of Economics, 1970)
I. Introduction and summary, 627. — II. Assumptions, 629. — III. The monopoly and purely competitive decisions, 631. — IV. The generality of the results, 633. — V. Some concluding remarks, 635. — Appendix (to Section III), 636.